Revitalizing Religious Moderation among Adolescent Santri:: A Community Service Initiative Integrating Counseling and Psychological Communication for Inclusive Character Building - Rofiqah, Rofiqah; Arifin, Zainul; Susanto, Djoko; Mas'ud, Mochamad (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: Strengthening the value of religious moderation is a strategic agenda in Islamic boarding school education, especially among adolescent students who are vulnerable to the influence of extreme ideologies and the unfiltered flow of digital information. Purpose of the Study: This Qaryah Thayyibah-based community service program aims to revitalize the value of religious moderation among adolescent students at the Nurul Muttaqin Islamic Boarding School in Malang through the integration of psychological counseling and communication. Methods: The implementation method includes four stages: (1) assessing students' needs to identify challenges related to religious moderation; (2) psychologically based individual and group counseling focusing on emotional management, strengthening self-identity, and problem-solving skills; (3) focus group discussions (FGDs) emphasizing reflection on the values ​​of tolerance, balance, justice, and deliberation; and (4) effective communication simulations that foster empathy, openness, and respect for differences. Results: The results of the activity indicate a significant increase in students' understanding of the principles of religious moderation, healthy communication skills, and the ability to manage differences constructively. Counseling has proven effective in helping students reflect on their spiritual and social experiences, fostering a new awareness of the importance of living a moderate, peaceful, and inclusive life. These findings demonstrate the contribution of community service in building the character of adolescent students based on Islamic values ​​of rahmatan lil 'alamin (blessing for the universe) while strengthening a harmonious pesantren culture.